Colombia and the Regional South-South International Cooperation: an experience of innovation and international positioning - Nivia-Ruiz, Fernando; Prieto Cardozo, Jorge (Revista Española de Desarrollo y Cooperación, 2023)
The region of Latin America and the Caribbean has been prominent as a leading actor in the development and implementation of the South-South Cooperation. Recently, Colombia has shown remarkable signs of progress while structuring cooperation processes beyond the traditional bilateral SSC relations, such as the South-South Cooperation Regional Strategies not only among the Latin America and the Caribbean region but also in Asia and Africa. There are already evident achievements, but also significant challenges to overcome.
Keywords: Colombia; Regional South-South Cooperation; Positioning